Marine water bioremediators: Sustainable solutions for pollution reduction - Kodić, Rafaela; Kalambura, Sanja (Crisis Management Days, 2025)
Marine water pollution represents one of the most critical environmental challenges today. Increased industrial development, urbanization, and tourism expansion significantly contribute to the introduction of toxic substances into marine ecosystems, including heavy metals (e.g., mercury, cadmium, lead), organic pollutants (such as polycyclic aromatic hydrocarbons - PAHs and pesticides), and nutrients causing eutrophication. Traditional purification methods, such as chemical treatments and physical processes (filtration, sedimentation), are often costly, energy-intensive, and may lead to secondary pollution. Therefore, biological purifiers (bioremediators) emerge as a sustainable and environmentally friendly solution. Bioremediators utilize microorganisms (bacteria, archaea, fungi), algae, and plants that, through natural metabolic processes, degrade or remove pollutants from marine water. Key bioremediation methods include: Bioremediation – the use of specific microorganisms like Pseudomonas putida or Alcanivorax borkumensis to degrade organic pollutants such as petroleum derivatives. Phytoremediation – the use of macroalgae (Ulva, Gracilaria) and seagrasses (Posidonia oceanica) to absorb heavy metals and excess nutrients. Biosorption – the application of biomass (living or dead) to bind heavy metals from water. Biofiltration – the use of microbial biofilms attached to substrates to remove suspended particles and dissolved contaminants. The aim of this paper is to investigate the efficiency of bioremediators in removing specific pollutants and to analyze their mechanisms of action in marine environments. Special emphasis is placed on the removal capabilities of heavy metals, nutrients (nitrogen and phosphorus), and organic contaminants. The research examines various types of bioremediators and their application in real ecosystems, such as marinas, ports, and areas affected by oil spills. Results indicate that bioremediators can significantly reduce pollutant concentrations in marine ecosystems with minimal environmental impact. For example, the application of Alcanivorax borkumensis has proven effective in degrading hydrocarbons after oil spills, while macroalgae successfully removed excess nutrients in eutrophic areas. Despite these successes, challenges such as optimizing the efficiency of bioremediators under different ecological conditions and adapting them to specific types of pollution still require further research. The development of hybrid systems that combine biological, chemical, and physical methods could further enhance process efficiency. Bioremediators represent a promising solution for the preservation of marine ecosystems, enabling sustainable management of marine resources and reducing the ecological footprint of industrial and urban areas.